Vital Signs Detection With Difference Beamforming and Orthogonal Projection Filter Based on SIMO-FMCW Radar - Xiong, Junjun; Hong, Hong; Xiao, Lei; Wang, E.; Zhu, Xiaohua (IEEE transactions on microwave theory and techniques, 2023)
Noncontact vital signs detection based on radar has attracted a lot of interest in recent years. Many efforts have been made to make this technology more complete. However, there still exist some challenges, such as vital signs detection of two closely positioned subjects and heart rate estimation with the interference of the high-order respiration harmonics. This article designs a single-input multiple-output (SIMO) frequency-modulated continuous-wave (FMCW) radar. Based on this system, difference beamforming and orthogonal projection filter (OPF) have been proposed to solve the two challenges. Difference beamforming is able to separate the vital signs of the two subjects even if the angular difference between the two subjects is smaller than the angular resolution of the array antenna. OPF can remove the high-order respiration harmonics without complex parameter adjustment operations and tedious calculations. The experimental results show that the proposed algorithm can successfully separate the vital signs of two closely positioned subjects and estimate the heart rate accurately with the interference of high-order respiration harmonics. The results also verify that the designed SIMO FMCW radar can separate the vital signs of subjects at different distances.